Penerima Sinyal Emergency Locator Transmitter dengan Metode Direct Receiver pada Frekuensi 121,5 MHz (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2020)
To find out the location of an aircraft accident from an ELT signal beam of 121.5 MHz, search and rescue (SAR) officers or civil aviation authorities need an ELT signal receiver device that works at the same frequency, which is 121.5 MHz. The purpose of this research is to produce an ELT signal receiver with direct receiver method at a frequency of 121.5 MHz which is simpler, requires fewer RF devices, and is according to specifications for civil aviation. In this research, the design and realization of ELT signal receivers are carried out using the direct receiver method, including: a BPF and a RF amplifier as a direct receiver circuit, an AM demodulator, and an audio amplifier. Based on the results of measurements and tests that have been done, the direct receiver circuit can receive an ELT signal at a frequency of 121.5 MHz in the range of 121.330 to 121.617 MHz with -40.35 dB sensitivity, the AM demodulator can demodulate the audio signal at a frequency of 346.6 Hz, and the audio signal at a frequency of 337.6 Hz as a pointer to an ELT signal can be heard through the loudspeaker. The results of this study are ELT signal receivers with direct receiver method at a frequency of 121.5 MHz which are according to specifications for civil aviation.